Effects of Subthreshold Shocks on Wavelet Propagation during Atrial Fibrillation in Humans - Barbaro, V.; Bartolini, P.; Calcagnini, G.; Censi, F.; Macioce, R.; Michelucci, A.; Poli, S. (Methods of Information in Medicine, 2004)
Objectives: Our objectives are: first to investigate the effects of internal cardioversion energies on the wave fronts propagation in the right atrium immediately after the energy delivery; second, to track the time course of these effects.Methods: The study is based on a measure of organization of the endoatrial electrograms obtained by a multipolar basket catheter inserted in the right atrium. We estimated the level of organization by computing the percentage of points laying on the signal baseline (i.e., number of occurrences, NO). NO values were computed on two-second long windows. Six non-overlapped windows were selected, one just before and five just after the last unsuccessful shock.Results: Immediately after the shock most of the patients exhibited an increase in the organization patterns. This increase was more evident in those patients with rather disorganized patterns and higher energy threshold. This effect fades within a few seconds after the shock delivery.Conclusions: Our data confirm the idea that the electrical shock causes a widespread extinction of electrical wavefronts, which regenerates after the shock. Since an increase of organization may lead to a reduction of energy threshold, a potential application of these findings might consist in the delivery of multiple subthreshold shocks instead of a single one.
Keywords: Atrial fibrillation; electrogram analysis; internal cardio-version; organization